Niche-related processes explain phylogenetic structure of acoustic bird communities in Mexico - Christian D. Morán-Titla; Juan-Hector García-Chávez; Leonel Lopez-Toledo; Clementina González (PeerJ)
Acoustic communities are acoustically active species aggregations within a habitat, where vocal interactions between species can interfere their communication. The acoustic adaptation hypothesis (AAH) explains how the habitat favors the transmission of acoustic signals. To understand how bird acoustic communities are structured, we tested the effect of habitat structure on the phylogenetic structure, and on the phylogenetic and vocal diversity of acoustic communities in a semi-arid zone of Mexico. From autonomous recordings in three types of vegetation (crop fields, tetecheras, and mesquiteras), which differ in terms of complexity and canopy openness, we evaluated sound attenuation, and estimated metrics of phylogenetic structure and diversity as well as acoustic diversity with the use of two indices. Mesquiteras showed greater vegetation density, more attenuation, more vocal diversity, as well as a phylogenetic structure that tended towards overdispersion, in contrast to crop fields that showed less vegetation density, less attenuation, less vocal diversity and more phylogenetic relatedness, while tetecheras showed intermediate patterns. Phylogenetic structure was explained by vegetation density and excess attenuation. The higher vocal diversity, phylogenetic structure tended towards overdispersion. These results suggest a role for environmental filters in the crop fields, where more closely related species with similar vocal characteristics coexist (supporting AAH), and probably competitive exclusion in the mesquiteras, where more distantly related species coexist, promoting vocal diversity. This study offers information about the influence of habitat on the acoustic community structure, which could inform our understanding of the distribution of species from acoustic perspective.